The impact of patient navigation: a scoping review protocol. (June 2019) - Reid, Amy E.; Doucet, Shelley; Luke, Alison; Azar, Rima; Horsman, Amanda Rose
Abstract : Review objective/question: The objective of this review is to synthesize the evidence on the impact of patient navigation for all populations across all settings. The question of this review is: What is the existing evidence on the impact of patient navigation?